Roa Bastos's "Noche sin fin" ("Endless Night") and "La tijera" ("The Scissors"): Two Versions of the Same Story - Weldt-Basson, Helene C. (2002)
This study focuses on the manner in which Roa Bastos has transformed the short story "Noche sin fin", originally published in the journal Ficción (1957), into his history "La tijera", later published in his collection El baldío (1966).